Evaluation of temporal trends and correlations of physical-chemical parameters in vast oceanic areas robust to information uncertainty. (February 2023) - Borges, Carlos; Palma, Carla; Bettencourt da Silva, Ricardo J.N.
Abstract: The physical-chemical monitoring of vast oceanic areas aims at assessing the status and evolution of the environmental resource for its exploration, protection and/or better understanding. However, the interpretation of monitoring data is affected by ocean seasonality and heterogeneity, and by the quality of sampling and characterization tools used to study the environment. All these factors contribute to the uncertainty of collected information that should be expressed in determined parameter values or trends. A trend of a studied parameter quantified by values difference is significant if the observed absolute value of the difference is larger than their expanded uncertainty. The correlation of studied parameters, useful for their interpretation, is equality affected by the mentioned sources of uncertainty. This work describes the metrologically sound evaluation of trends and correlations of physicochemical parameters of vast oceanic areas where all uncertainty sources affecting the information are considered by simulating their complex impact by the Monte Carlo Method. The described methodology was successfully used to study the impact of summer upwelling in an 800 km 2 coastal area offshore two large cities in Portugal. Nutrients, conductivity, salinity and temperature trends and correlations are distinguished from system heterogeneity, sampling and sample analysis uncertainty for a 99% confidence level. Graphical abstract: Image 1 Highlights: Simulation of the impact of the heterogeneity, and sampling and analysis uncertainty on oceanic area characterisation. Mean value of nutrients and fundamental oceanographic parameters from a vast oceanic area reported with uncertainty. Evaluation of the variation of mean composition values between October 2019 and May 2018 for a 99% confidence level. Correlations between nutrients and fundamental oceanic parameters evaluated taking information uncertainty into account. Upwelling trends and correlations confirmed from modelled spatial variation of a vast oceanic area with uncertainty.